Agriculturar a agricultura: a modernização da agricultura no governo estadual paulista (1892-1926) - Henriques, Amilson Barbosa [UNESP] (2015)
This research seeks to understand and analyze the operating period of the Agriculture Department of São Paulo State between 1892's to 1926's. The main purposes are checking and analyzing the proposals and attempts to modernize the agriculture in the state. Such emphasis was highlighted and experienced during the second half of the 19th century entering the 20th century, being disclosed in publications in São Paulo, as well as with the Agriculture Department's uphold and support. The objective of this research is to highlight that the Agriculture Department of São Paulo developed, not an agricultural modernization strategy, but that during the period researched for its performance, this government body has encouraged and developed in several aspects the modernization presented by the elite of farmers in the State